Pemenuhan Kebutuhan Sistem Jaringan Air Bersih di Kota Baru Pattallassang, Kabupaten Gowa - Anggel Erpa Erong Pakiding; Rudi Latief; Muh. Idris Taking (Fakultas Teknik Universitas Bosowa, 2022)
Anggel Erpa Erong Pakiding, 2022. Fulfilling the Need for a Clean Water Network System in Pattallassang New Town, Gowa Regency. Supervised by Rudi Latief and Idris Taking. The purpose of this study was to determine the cause of the unfulfilled need for clean water and to determine the need for a clean water network system in Pattallassang New Town, especially in Paccelekang Village. This study uses quantitative and qualitative methods that use scoring analysis to determine scores on respondents' answers and descriptive analysis, by verbally describing the data on symptoms that appear in the research area. The conclusion of this study is that the main cause of the unfulfilled need for clean water at several points in the research area is due to the pressure and air storage capacity that cannot accommodate optimally and the condition of the research area which is in the border area. Thus, to meet the need for clean water in Kota Baru Pattalassang, namely by using pipeline system technology using a branch system (branch system).